Rabies in Indonesia and The Development of Its:Diagnostic Techniques - R M A Adjid; A Sarosa; T Syafriati; Yuningsih . (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2005)
Rabies is a zoonotic disease which is crucial for public health, as it can infect human beings and causes death . Rabies has spread across the world including Indonesia . Control to erradicate rabies still faces many obstacles. Rabies research at Research Institute for Veterinary Science emphasizes on rabies erradication focussing on some aspects of diagnostic techniques. Studies on the spesimen preservation, the shipment to the laboratory and the collection of brain specimens by straw method as well as the use of cornea touch preparat as intra vitam specimens have been conducted. Rabies diagnostic techniques by NPLA or modified FAVN on multispot slides and their applications in the field have also been studied. This paper also describes the preparation of FITC conjugate. ELISA technique was developed for serological test but still need to be improved to reduce non specific reaction, while RREID was used for antigen detection. Rabies diagnostic was conducted by using RT-PCR but its application was very difficult to be done for intra vitam. Research on Croton tiglium and Pangium edule extracts as an alternative for the strychnine poison used for dog elimination in the field has also been conducted but further research is needed in the future. Key words: Rabies, zoonosis, research, diagnostic